Customer Value Assessment for Value-Based Pricing - Gale, Bradley T. (Henry Stewart Talks, 2011)
Targeting Price and Performance Levels, Managing Customer Value, Performance for Price, Customer Value Map, Customer Value Mapping, Relative Value, Goodness of Deal, Price-Performance Curve, Fair-Value Price, Neutral Price, Value-Based Pricing, Comparative Performance Scorecard, Assemble Performance Measures, Components of Overall Performance, Key Buying Factors, Benefit Attributes, Product & Service Attributes, Attribute-Level Performance, Alternative Products, Performance Evaluation Standards, Product Differentiation, Product Appraisal Table, Assess Competitive Value, Customer Value Assessment, Attribute Importance Weights, Benefit Segmentation, Price-Performance Sensitivity, Product Strategy Decisions, Simulating Performance Changes, Targeting Benefit Segments, Developing Successful Product Strategies, Customer Value Management